The Effect of Soil Chemical and Physical Characteristics on Growth of 30 Families of Teak (Tectona grandis) in a 10-year-old Progeny Test - Daryono Prehaten; Sapto Indrioko; Suryo Hardiwinoto; Mohammad Na'iem; Haryono Supriyo (Jurnal Ilmu Kehutanan)
Some environmental factors that greatly affect plant growth are soil’s physical and chemical properties. Some teak families planted at different locations alleged to have different growth responses. This study aimed to investigate the growth response of teak (height and diameter) from 30 families, and to determine the effect of soil chemical and physical characteristics on teak growth in two different locations. Teaks were measured for total height and diameter at breast height. Soil pits (size: 1 m x 1 m and 1 m in depth) were dug and samples were taken from 0-10 cm, 10-20 cm, 20-40 cm and 40-60 cm in depth. Soil characteristics measurement were conducted on pH (H2O), organic carbon, total Nitrogen, available P, K, Ca, and Mg, also the Cation Exchange Capacity (CEC). Further, soil physical properties been measured was soil texture. Statistical analysis was performed by t- test. The results showed that teak’s diameter of all 30 families, showed significant differences between the two locations, while only a small proportion of height parameters significantly differed among families. Chemical and physical characters of the soil also showed differences between the two locations. Soil pH (H2O), available K, Ca, and Mg, were significantly differed between the two locations while the content of organic C, available P and the CEC were not significantly differed. For the soil physical properties, content of clay and silt in two location significantly differed whereas the sand content did not differ significantly. These differences indicate that some properties of the soil were affecting the growth response of teak famili in terms of both height and diameter.